Biodiesel Generation from Palm Kernel Biomass via an In-situ Transesterification Approach - Ikechukwu, Chikaodili D; Ifijen, Ikhazuagbe H; Udokpoh, Nyaknno U. (Tanzania Journal of Science, 2021)
This study investigated an in-situ transesterification of palm kernel biomass at variable reaction times (4 h, 5 h and 6 h) and catalyst loading (2 wt%, 3 wt.% and 5 wt.%). The biodiesel yields were observed to vary with these parameters. GC-MS analysis showed high fatty acid methyl esters (FAMEs) contents for all the prepared biodiesel samples (C-18:1, C-14:0, C-16:0, and C-18:0). 2 wt.% catalyst loading and 4 h reaction time were observed to be the best reaction conditions from the experimented parameters that gave the best biodiesel yield at 300 rpm mixing intensity. The in-situ method recorded a higher degree of oil extraction and efficient conversion of oil to biodiesel (93.93%) compared to the conventional transesterification method which gave 89.45%. The kinematic viscosity, acid value and iodine value of 3.96 mm2/s, 0.56 mg KOH g–1 and 120 g 100 g–1 were found to be within the limits of ASTM D6751-09 and EN14214 standards. These results confirm that efficient production of biodiesel from palm kernel biomass could be possible through an in-situ acidic transesterification process. Keywords: Biodiesel, fatty acid methyl ester, palm kernel biomass, transesterification